2020
DOI: 10.12775/jehs.2020.10.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation after ischemic stroke in the elderly

Abstract: The presented methods of improving NDT Bobath, PNF and motor imagery are more effective in the treatment of people after ischemic stroke in the elderly than traditional methods of treatment. Research that was used for the purposes of this article conducted in the years 2009-2015 prove the effectiveness of these methods. Conclusions Based on the research carried out so far, the effectiveness of the given methods on the process of rehabilitation of a patient after a stroke can be confirmed. The use of both basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Following the same line of thought, the intervention based on this methodology follows several steps, starting with positioning in a phase of sagging (after the occurrence of stroke), postural control and normalization of the tone (spasticity phase), and normalization of normal movement patterns. 2 In the study The influence of NDT-Bobath and PNF methods on the field support and total path length measure foot pressure (COP) in patients after stroke, authors concluded for a greater improvement, concerning the body balance, with the Bobath approach. 30 The literature review suggests that the intervention of the occupational therapist should meet the needs of the patient and that this intervention should be evaluated and reevaluated at each stage of the rehabilitation process, to provide the appropriate treatment to each patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Following the same line of thought, the intervention based on this methodology follows several steps, starting with positioning in a phase of sagging (after the occurrence of stroke), postural control and normalization of the tone (spasticity phase), and normalization of normal movement patterns. 2 In the study The influence of NDT-Bobath and PNF methods on the field support and total path length measure foot pressure (COP) in patients after stroke, authors concluded for a greater improvement, concerning the body balance, with the Bobath approach. 30 The literature review suggests that the intervention of the occupational therapist should meet the needs of the patient and that this intervention should be evaluated and reevaluated at each stage of the rehabilitation process, to provide the appropriate treatment to each patient.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] It aims to achieve normal patterns of movement, normalization of the tone, control of head and trunk and to minimize abnormal movement patterns. 2 For the application of this method, an in-depth knowledge about the normal sequential development of motor behavior is required. 17 The method under study also encourages bilateral use of the body to model pathological motor patterns and provide a relearning of movements.…”
Section: Issn: 2770-677xmentioning
confidence: 99%
See 2 more Smart Citations